Exploring Ideas Through Coffee for Cultivating Creativity - Maspul, Kurniawan Arif (Jurnal Psikologi, 2024)
The quest for fresh ideas is a continual process in our dynamic environment, which is driven by innovation. This study conducts a thorough investigation into the complex relationship between coffee culture and the creative process, recognizing the tremendous influence of human cognition and the fundamental human desire for novelty and expression. This qualitative study aims to uncover strategies that enable individuals to tap into their creative reservoirs and cultivate environments conducive to innovation by conducting a nuanced examination of coffee settings and their multifaceted influence on cognitive processes, social dynamics, and environmental cues. This study provides a deeper understanding of how coffee-fueled environments can serve as catalysts for creativity, fostering transformative advancements across various domains and enriching the human experience by combining insights from diverse disciplines and leveraging real-world examples from the coffee industry.